Effects of Criminogenic Risk–Needs Assessment Feedback During Prerelease Correctional Rehabilitation - King, Christopher M. (Criminal justice and behavior, 2021)
This pre–post follow-up randomized trial investigated the receptiveness and responsiveness of 82 incarcerated men undergoing reentry to feedback (discussion-based, form-based, or none–minimal) regarding their criminogenic risk–needs assessment results. Both short-term outcomes (self-perceived risk–needs, motivation for change, treatment readiness, and feedback satisfaction) and longer-term outcomes (intuitional conduct, rearrest, or halfway house return) were examined. As hypothesized, among study completers (n = 67), motivation for change was significantly higher following discussion feedback, and both feedback formats were rated favorably by participants. Contrary to hypotheses, feedback recipients, including those who showed gains at post, did not appear reliably distinct from others on longer-term outcomes; nor were most outcomes significantly associated with baseline risk scores. Feedback about risk and needs may be useful in correctional treatment for motivation enhancement and treatment orienting, but special attention to measurement, contextual, and intensity factors is warranted.